Probing the He ii re-Ionization ERa via Absorbing C iv Historical Yield (HIERACHY) I: A strong outflow from a z ∼ 4.7 quasar. Issue 3 (5th June 2021) - Yu, Xiaodi; Li, Jiang-Tao; Qu, Zhijie; Roederer, Ian U; Bregman, Joel N; Fan, Xiaohui; Fang, Taotao; Johnson, Sean D; Wang, Feige; Yang, Jinyi
ABSTRACT: Outflows from supermassive black holes (SMBHs) play an important role in the co-evolution of themselves, their host galaxies, and the larger scale environments. Such outflows are often characterized by emission and absorption lines in various bands and in a wide velocity range blueshifted from the systematic redshift of the host quasar. In this paper, we report a strong broad line region (BLR) outflow from the z ≈ 4.7 quasar BR 1202-0725 based on the high-resolution optical spectrum taken with the Magellan Inamori Kyocera Echelle (MIKE) spectrograph installed on the 6.5 m Magellan/Clay telescope, obtained from the 'Probing the He ii re-Ionization ERa via Absorbing C iv Historical Yield' (HIERACHY) project. This rest-frame ultraviolet (UV) spectrum is characterized by a few significantly blueshifted broad emission lines from high ions; the most significant one is the C iv line at a velocity of -6500 km s −1 relative to the H α emission line, which is among the highest velocity BLR outflows in observed quasars at z > 4. The measured properties of UV emission lines from different ions, except for O i and Ly α, also follow a clear trend that higher ions tend to be broader and outflow at higher average velocities. There are multiple C iv and Si iv absorbing components identified on the blue wings of the corresponding emission lines, which may be produced by either the outflow or the intervening absorbers.